2006
DOI: 10.1021/nl060928a
|View full text |Cite
|
Sign up to set email alerts
|

V2O5 Nanorods on TiO2 Nanofibers: A New Class of Hierarchical Nanostructures Enabled by Electrospinning and Calcination

Abstract: Electrospinning provides a simple approach to fabricating nanofibers and assemblies with controllable hierarchical structures. In this communication, we demonstrate that electrospinning can be combined with calcination to further maneuver the morphology and phase structure of nanofibers. More specifically, single-crystal V2O5 nanorods could be grown on rutile nanofibers by carefully calcining composite nanofibers consisting of amorphous V2O5, amorphous TiO2, and poly(vinylpyrrolidone). The size of the resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
178
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(182 citation statements)
references
References 36 publications
3
178
0
1
Order By: Relevance
“…For example, a number of groups have demonstrated that electrospinning allows one to maneuver the secondary structures of individual fibers as well as to increase their structural complexity. (Ostermann et al, 2006,T.S.He et al, 2010,Cao et al, 2010,Wang et al, 2008 Here we demonstrate that electrospinning and sputter coating technique can be combined to provide a simple route to formed the 3D hierarchical structural Au/TiO 2 nanofibers. The structure of samples prepared at different Au depositing time were investigated.…”
Section: Introductionmentioning
confidence: 82%
“…For example, a number of groups have demonstrated that electrospinning allows one to maneuver the secondary structures of individual fibers as well as to increase their structural complexity. (Ostermann et al, 2006,T.S.He et al, 2010,Cao et al, 2010,Wang et al, 2008 Here we demonstrate that electrospinning and sputter coating technique can be combined to provide a simple route to formed the 3D hierarchical structural Au/TiO 2 nanofibers. The structure of samples prepared at different Au depositing time were investigated.…”
Section: Introductionmentioning
confidence: 82%
“…Electrospinning seems to be the simplest and most versatile technique for generating 1D nanostructures, particularly nanofibers with length up to hundreds of meters [138][139][140][141][142][143]. Fig.…”
Section: Electrospinning Of 1d Nanostructuresmentioning
confidence: 99%
“…Environmental problems such as air and water pollution have provided the impetus for sustained fundamental and applied research in the area of environmental remediation [139][140][141][142][143][144]. With the steady and fast growing field of nanoscience and nanotechnology, nanostructured ceramics like zinc oxide and titanium oxide has become a promising photocatalyst for its high catalytic activity, low cost, and environmental friendliness [50,51,55,57, Electrospinning ceramic nanofibers have extremely high surface area due to its small sizes, and further provide channels for quick charge transfer due to its 1D nanostructures.…”
Section: Photo Catalystmentioning
confidence: 99%